Snake fauna of the Andaman Islands, Bay of Bengal—A review of species richness, taxonomy, distribution, natural history and conservation status - Chandramouli, S.r. (Zootaxa, 2022)
The snake fauna of the Andaman archipelago was studied over a duration of four years across twenty islands. This paper presents information on the species richness and taxonomy of snakes of the Andaman archipelago along with observations on natural history and a review of their distribution records, including new, precise ones. Natural history observations for some of the recently re-evaluated species are presented herein for the first time. Field observations on snakes made during this study are supplemented with a compilation of data from specimen collections (n=34) examined in various museums. Based on this dataset and reliable, verified literature records, distribution maps are presented for all the snake species in the Andaman Islands. In addition, unsubstantiated old records of certain species that are shown to be ambiguous are removed from the updated checklist presented here, which consists of 23 species from 22 genera and eight families. Nine of these terrestrial (non-marine) species (56%) are endemic to the Andaman Islands. However, some of the non-endemic species are still in need of a proper molecular taxonomic assessment. The majority (70%) of species are of Least Concern, with 13% of the species being Data Deficient, 9% being Endangered, 5% of the species still in need of evaluation of their conservation status and 4% each being Near Threatened and Vulnerable.